Effets du semis direct et de l'irrigation d'appoint sur le rendement du blé dur et la fertilité du sol à la station expérimentale de Marchouch (Zaer-Maroc). - Rharbaje, Meryem (Institute of Agronomy and Veterinary Hassan II, 2022)
In Morocco, available water resources have diminished, which represents a major risk for food security. Hence the need to adopt an innovative and sustainable system (no tillage system). In this context, the main objective assigned to this work is to determine the effect of no tillage in interaction with different water regimes. To do this, we installed our trial at the Marchouch experimental station of ICARDA. The study focused on monitoring the effects of tillage mode (CT: Conventionnal tillage; NT: No tillage), and three water regimes (Rainfed ; 1IR : One irrigation ; 2IR : Two irrigations). With the aim of evaluating, on the one hand, the effect of these factors and their interactions on the yield of durum wheat and its components (number of ears/m², number of grains/ears and TGW, grain and straw yield ) as well as nutrient and water use efficiency. On the other hand, their effect on the chemical properties of the soil (rate of organic matter, phosphorus, potassium and nitrogen) in two soil horizons (0-15 cm and 15-30 cm) and on two similar, homogeneous plots which have not only undergone the same technical itinerary but also have the same cultural precedents in recent years. The results of this study have in particular made it possible to demonstrate that the mode of tillage affects grain yield and straw yield. Let us add that the NT acts favorably on the normalized vegetation index (NDVI). Through the analysis of the results obtained, it seems that irrigation is essential in the context of drought in 2021/2022 for improving the yield of durum wheat, its growth and has a significant effect on the water use efficiency. It can be said that a second irrigation supply acts favorably and has a positive effect on yields under NT (3157.76 kg/ha) and on yield components in particular (the highest values are recorded under this amount of irrigation supply for: the number of grains/ear 29.28 grains/ear and TWG 45.98g). The water regime also acts on the chemical properties of the soil, in particular the nitrogen content (42.56 mg/kg). In conclusion, no-till systems have promising effects on yield in the context of the drought experienced by Morocco this year.